Analisis Kesulitan Belajar Siswa Kelas X IPA di SMA Negeri 3 Tebas pada Materi Protista - Hisdayu Hisdayu; Titin Titin; Andi Besse Tenriawaru (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Biology is considered difficult for students to study, this condition cannot be separated from the nature of science. Studying science is complex because it emphasizes unification, systematization, combination and analysis of information and concepts. The aim of this research is to measure the level of learning difficulties experienced by class X Science students on Protista material. The method used is a case study. The research subjects were students of class X Science at SMA Negeri 3 Tebas, Sambas Regency. Data collection instruments consist of diagnostic tests, questionnaires and interviews. The results of the research showed that the learning difficulty of class X Science students at SMA Negeri 3 Tebas on Protista material was 91.94% with very high criteria. The factors that influence students' learning difficulties are internal factors of 78.18% with strong criteria, and external factors of 64.14% with strong criteria.